Disruption In The Industrialized Higher Education Has An Impact On The Quality Of Higher Education And Also The Human Resources Of Their Graduates - Yasrie, Arfie (Journal of Educational Management Research, 2025)
This study explores the profound impact of the disruption caused by the industrialization of higher education on the quality of educational institutions and the human resources (HR) of their graduates. Employing a descriptive exploratory approach, the research combines a comprehensive literature review with direct observations of the subjects involved. The descriptive method aims to illustrate the challenges and phenomena arising from the industrialization of higher education, while the exploratory approach delves into the conceptual underpinnings of this disruption. The literature review draws upon scientific journals, books, and online resources to gather relevant data, while participant observation provides firsthand insights from the researcher's experience as a lecturer. The findings reveal that the industrialization of higher education has significantly influenced both the quality of academic institutions and the capabilities of their graduates. The study concludes with recommendations for governments and educational bodies to enhance the quality of higher education and its graduates, ensuring they are better equipped to compete in the global workforce.